Study of Optical Soliton Perturbation with Quadratic-Cubic Nonlinearity by Lie Symmetry and Group Invariance - Asma, Mir; Bansal, Anupma; Othman, Wan Ainun Mior; Wong, Bernardine Renaldo; Biswas, Anjan (Springer Verlag, 2018)
Here, optical soliton perturbation with quadratic-cubic nonlinearity has been discussed by applying Lie symmetry and group invariants. The perturbation terms include third and fourth order dispersions in addition to self-steepening, intermodal dispersion and higher order dispersion effects. Using presented algorithms, Bright and dark soliton solutions are revealed.